Sustainable Vegetable Oil Systems and SDG Indicators in Major Producing Countries - Nurachmat Herlambang; Zulkifli Alamsyah; Dompak Napitupulu; Adriani Adriani; Mirawati Yanita; Karina Rahmah (Postgraduate, University of Mataram, 2026)
This study examines the relationship between vegetable oil systems and Sustainable Development Goals (SDGs) indicators in major producing countries. The research focuses on palm oil and soybean oil as strategic global commodities that contribute to food security, employment, and economic sustainability. Secondary data were collected from international databases, including the World Bank, FAOSTAT, and USDA, covering major producer countries over a multi-year period. The analysis evaluates the interaction between vegetable oil production, trade dynamics, and selected SDG indicators related to poverty reduction, food availability, inequality, and economic growth. The findings indicate that vegetable oil development plays an important role in supporting national economic performance and improving several SDG indicators, although the impacts differ across countries depending on production structure, export orientation, and domestic policy conditions. Palm oil-producing countries showed stronger contributions to employment generation and export growth, while soybean-producing countries demonstrated greater stability in food supply systems. The study concludes that sustainable vegetable oil governance is essential to balance economic development, environmental sustainability, and social welfare in achieving the SDGs. These findings provide important insights for policymakers in designing sustainable agricultural and trade policies